Dynamics and Transformation of Da'wah in Manado During Covid-19 Pandemic - Rusdiyanyo Rusdiyanto (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This article reviews the dynamics of Islamic da'wah in Manado before and during the COVID-19 pandemic. The question posed by this article is: what were the dynamics of Islamic da'wah in Manado before the COVID-19 pandemic? And how is the transformation of da'wah during the COVID-19 pandemic? Using a historical approach, the author finds two things: First, historically, Islamic da'wah in Manado has taken place simultaneously with the process of Islamization that occurred since the beginning of the 17th century, but da'wah and Islamization began to be massive and had a dominant impact on the development of Islam in Manado since the placement of exiles by the colonial. With the adaptation process, these figures were able to carry out cultural da'wah in Minahasa and Manado. The success of Islamic da'wah in the city of Manado is also inseparable from the role of Islamic organizations such as Alkhairaat, Muhammdiyah, and Nahldatul Ulama. These three organizations do a lot of da'wah through formal education channels by establishing schools, madrassas, and pesantren. Second, during the COVID-19 pandemic, there were no digital da'wah activities that were carried out regularly and systematically and were open to the public by da'wah actors in Manado, both individually and organizationally. Most da'wah practitioners in Manado move individually and are partial, meaning that each dai carries out their da'wah activities individually based on their respective popularity in the community.